Strengthening Halal MSMEs through Triple Helix Collaboration: A SWOT-Based Analysis in Yogyakarta - Munir Azhari (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
This study examines the development of halal Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta by analyzing the interaction between institutional actors and internal business capacity. Despite the rapid growth of the global halal industry, the number of halal-certified MSMEs in Yogyakarta remains relatively low, indicating the presence of structural challenges. This research employs a qualitative descriptive approach, utilizing data collected through interviews, observations, and literature review. The analytical framework combines the Triple Helix model, which explores the roles of academics, business actors, and government, with SWOT analysis to identify internal and external factors influencing MSME development. The findings reveal a significant gap between high market opportunities and the limited readiness of MSMEs, particularly in terms of halal literacy, technological capability, and managerial capacity. Although the Triple Helix framework has been implemented, collaboration among actors tends to be programmatic and has not yet formed a sustainable development ecosystem. As a result, MSMEs face difficulties in transforming market potential into competitive advantage. This study argues that strengthening halal MSMEs requires not only regulatory support and capital assistance but also an integrated strategy that emphasizes capacity building, institutional collaboration, and market-oriented innovation. The findings contribute to the discourse on MSME development by highlighting the importance of systemic collaboration in enhancing the competitiveness of halal-based enterprises.